Observational study of river-land breeze and its influence on distribution of PM10 concentrations over a main mining city in the Yangtze River Delta, China - Zhang, Hong; Wang, Xinqi; Hong, Xingyuan; Wang, Shuibin; Huang, Yong (Frontiers in Earth Science, 2023)
Wind data from air pollutant observation networks and meteorological stations are used to analyze the characteristics of river-land breeze near Tongling city (a main mining city in the Yangtze River Delta). The inhomogeneous distribution of pollutant matters near Tongling city due to river-land breeze is also investigated. Our results show the following conclusions. 1) The river breeze during the daytime is stronger than the land breeze at night. And the speed of river-land breeze is increased rapidly from 7:00 and arrived at the maximum at 12:00. After 15:00, the speed is slowed rapidly. 2) The river-land breeze in city area (east of Yangtze River, speed is .07 m/s) is weaker than the natural area (west of Yangtze River, speed is 0.18 m/s). Furthermore, the seasonal variations of breeze both in the west and east sides are different. In west side, the breeze is strongest in spring. And in the east side, the breeze is strongest in summer. 3) Under a weak breeze (≤0.45 m/s), the PM10 is moved by the breeze within the region and causes the heterogeneity. While with a strong breeze (>0.45 m/s), the PM10 is transported out of the region, and the PM10 concentration becomes homogenous. 4) The river breeze leads to a reduction of the pollutant concentration near the Yangtze River, but an increase in the city due to the transportation of pollutant particles from coast to city at daytime.